Increasing Throughput in Many Applications: Combining advanced motion controllers and highly accurate and dynamic positioning stages gives an edge to systems integrators and equipment manufacturers. Issue 2 (14th April 2021) - Simon, Markus; Vorndran, Stefan
Abstract: Cutting, drilling, welding, marking or structuring – lasers are used in a wide variety of applications in many industrial sectors to optimize manufacturing processes and satisfy the need for an ever increasing quality of components. This is especially true for the electronics and semiconductor industry, where requirements for accuracy and speed are higher than in most other applications.